2020
DOI: 10.20473/fmi.v56i3.22186
|View full text |Cite
|
Sign up to set email alerts
|

Blood Type and Blood Pressure Correlations to Body Mass Index in Young Adults

Abstract: Specific ABO blood type was reported to the higher risk of having overweight and obesity. The laters had also been suggested to correlate to blood pressure. Here we studied blood type and blood pressure amongst seemingly healthy university students of IIKBW, Kediri to understand their correlations to the body mass index (BMI). The blood typing (ABO typing, Eryclone®) and blood pressure (automated digital sphygmomanometer) of 74 male and 76 female were measured in duplicate accordingly. The BMI was analysed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The present study revealed a statistically significant difference only in ABO/ Rh blood group percentages (Rh +ve & Rh -ve) among pre-and post-menopausal hypertensive women. However, no statistically significant association between ABO/ Rh blood groups and hypertension indices was obtained which was consistent with recent findings [24,[27][28][29]. This highlights the complex interplay between biological factors, particularly hormonal changes, genetic factor, cardiovascular, demographic, and sample-related factors [10].…”
Section: Disscusionsupporting
confidence: 88%
“…The present study revealed a statistically significant difference only in ABO/ Rh blood group percentages (Rh +ve & Rh -ve) among pre-and post-menopausal hypertensive women. However, no statistically significant association between ABO/ Rh blood groups and hypertension indices was obtained which was consistent with recent findings [24,[27][28][29]. This highlights the complex interplay between biological factors, particularly hormonal changes, genetic factor, cardiovascular, demographic, and sample-related factors [10].…”
Section: Disscusionsupporting
confidence: 88%
“…The absence of blood group B may be due to their small number. The Indonesian (n=44), Myanmar (n=439), and Nigerian (n=439) had the frequency of O>B>A>AB, which agrees [46][47][48], and disagrees [49,50], with their countries results. In Indonesia, the frequency was B>O>AB>A [49], and in Nigeria, it was O>A>B>AB [50].…”
Section: Discussionmentioning
confidence: 95%